Parallels between experimental and natural evolution of legume symbionts - Camille Clerissi (Nature Portfolio, 2018)
It is unclear if experimental evolution is a good model for natural processes. Here, Clerissi et al. find parallels between the evolution of symbiosis in rhizobia after horizontal transfer of a plasmid over 10 million years ago and experimentally evolved symbionts.